A novel experimental system for the exploration of CO2-water-rock interactions under conditions relevant to CO2 geological storage - Rendel, P.; Wolff-Boenisch, Domenik; Gavrieli, I.; Ganor, J. (Elsevier BV, 2018)
This paper describes the design and experimental validation of a novel flow-through reactor system conceived for experimental studies to determine the kinetics and thermodynamics of mineral precipitation and dissolution in environmental conditions relevant to CO 2 geological storage. The experimental system was designed to work under a confining pressure of up to 150 bar, temperature up to 150 °C and corrosive conditions. The unique design allows the injection of precise amounts of liquid CO 2 into the reactor while avoiding the formation of multiple CO 2 phases. The modular design enables the in-situ measurement of pH using a pressure resistant in-line probe and electronic gauges which record pressure and temperature at multiple points. The system enables the user to withdraw liquid samples without disturbing the experimental conditions in the reactor. Customized computer software was developed and connected to the system to provide automatic data-logging capabilities, remote process control and the ability to partially shut-down the system in case of safety issues.